Tahapan Kegiatan dan Kendala Pelaksanaan Program UPPO pada Subak Abian Suka Maju di Desa Landih, Kecamatan Bangli, Kabupaten Bangli - I WAYAN EKA MULIAWAN; NI WAYAN SRI ASTITI; I GEDE SETIAWAN ADI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Procedures and Obstacles in The Implementation of Organic FertilizerProduction Unit in SubakAbianSukaMaju at Landih Village, Bangli District, Bangli RegencyThe Organic Fertilizer Production Unit (UPPO) is one of the government’s efforts to support the supply availability of organic fertilizer for farmers. The purpose ofthe research is to know the procedures and obstacles of UPPO programimplementation in SubakAbian (Traditional Agrarian Organization) SukaMaju atLandih Village, Bangli District, Bangli Regency. The data was collected throughinterview and documentation. 48 respondents were determined through purposivesampling method. The instrument of the research used questionnaires andinterview guidelines. The analysis method was descriptive qualitative analysis. The procedure of UPPO at SubakAbianSukaMaju began from the preparationstage which consists of socialization, agreement making, and organizationforming. After the preparation stage, comes the execution stage which consists oflocation determination, infrastructure construction, cage construction, livestockpurchasing, and facilities preparation. The last stage is the production, such as thelivestock sales benefit and manure. The execution stage is categorized as goodbecause the facilities well-supported the activity. The obstacles of the programimplementation are such as technical issues in preparing the infrastructures andfacilities, economic issues in allocating the aid fund as well as the return of cow sales benefit. There are also several social issues such as the low education of themembers, weak aspiration of the members, no leader figure within the society, andthe lack of innovation.It is recommended for the government to better monitor theUPPO program implementation, to mentor and assist the farmers, and to completethe infrastructure and facilities that the UPPO lack of, such as the fermentationtub, three-wheel vehicles, organic fertilizer manufacturing machines, animals’health certificate, and medicines for the livestock.